Faktor Yang Berhubungan Dengan Kepatuhan Pengobatan Pada Penderita Diabetes Mellitus(Dm) Tipe Ii Di Wilayah Kerja Puskesmas Purwodiningratan Surakarta - Septiyani, Linda, Heru Subaris Kasjono, SKM, M.Kes, Kusuma Estu Werdani, SKM, M.Kes (2016)
Diabetes Mellitus type II is chronic deficiency disease, absolute insulin resistency or relative, characterized by carbohydrate , protein and fat metabolic disorders, insulin resistency with variated defect degree of insulin secretion. Diabetes is one of the main causes death in the world. The prevalence of DM type II in work area of Puskesmas Purwodiningratan in 2014 (74,8%) was higher than in 2012 (4,08%). The aims of this study is to analize the correlation between patient intention, patient attitude, husband support, and patient belief with treatment adherence in diabetes melitus type II patient in the work area of Puskesmas Purwodiningratan Surakarta. The method of this research is observation using cross sectional. Population of this study was all the woman patient which adhere or not to the treatment of DM type II in 2015. The sample options amounts 71 people which are done by using Purposive Sampling whereas the statistic test is using Chi Square.. The result of bivariate analysis shows that there are correlation between patient intention (p=0,024;OR=3,900; 95%CI=1,143-13,311), correlation between patient attitude (p=0,018;OR=4,182; 95%CI=1,214-14,408), no correlation between husband support (p=0,614;OR=1,455; 95%CI=0,337-6,274), and no correlation between patient belief (p=0,674;OR=0,777; 95%CI=0,239-2,525) with treatment adherence in DM type II patient in the work area of Puskesmas Purwodiningratan Surakarta.